Identification of a novel homozygous SLC13A5 nonstop mutation in a Chinese family with epileptic encephalopathy and developmental delay - He, Hua; Long, Lijuan; Tang, Manling; Xu, Qiang; Duan, Shengwu; Chen, Ge; Zhao, Yan; Wu, Qiongfang; Chen, Jia (Frontiers in Genetics, 2025)
IntroductionBiallelic loss-of-function variants in the SLC13A5 (solute carrier family 13, member 5) gene are responsible for autosomal recessive developmental and epileptic encephalopathy 25 with amelogenesis imperfecta (DEE25). Until now, no pathogenic variants of SLC13A5 has been reported among the Chinese population.MethodsA Chinese Han pediatric patient with epilepsy and global developmental delay was described in this study. Trio-whole exome sequencing (WES) including the patient and her parents was performed to determine the genetic basis of the phenotype. Potential pathogenic variants were subsequently confirmed by Sanger sequencing. Additionally, we conducted an extensive review of the literature regarding SLC13A5 variants to analyze their associated phenotypic characteristics.ResultsTrio-WES revealed a novel homozygous variant c.1705T>G in SLC13A5 associated with clinical manifestations in the proband. The variant was also detected in her parents and unaffected sister, who were both heterozygous carriers. The variant is a nonstop substitution that is predicted to extend the SLC13A5 protein by 174 amino acids (p.569Gluext174). Analysis of previously published cases indicated that SLC13A5 patient in our study exhibited overlapping symptoms.DiscussionWe identified a novel homozygous nonstop mutation in the SLC13A5 gene of a Chinese patient with DEE25. This study expands the mutation spectrum of SLC13A5 and will have significant implications for the proband’s family in terms of medical management and genetic counseling.